2019
DOI: 10.1002/tesj.486
|View full text |Cite
|
Sign up to set email alerts
|

Focus on form options in second language pronunciation instruction: The case of lexical stress

Abstract: Pronunciation instruction has historically been notorious for its intense reliance on repetition practice and mechanical drilling across most foreign and second language settings.However, research indicates that form-focused instruction can be substantially beneficial to the development of phonological skills (Saito, 2012). The current quasi-experimental study builds on this strand of research by measuring the impact of focus on form (FonF) on English as a foreign language learners' retention of English word s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Since the aim in FoF is to afford students to be able to make discoveries through getting engaged in the language learning process actively (Coşgun Ögeyik, 2018), corrective feedback plays a major role to enable the students to uptake their intake (Sheen, 2004). Previous studies revealed the possible link between corrective feedback and the uptake in different areas of language; for example, pronunciation (Sheen, 2004), lexical stress (Hassanzadeh & Salehizadeh, 2020), and identifying lexical categories in a virtual environment (Akiyama, 2019). Evaluating this particular link, revision through corrective feedback contributes to students' writing considerably.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since the aim in FoF is to afford students to be able to make discoveries through getting engaged in the language learning process actively (Coşgun Ögeyik, 2018), corrective feedback plays a major role to enable the students to uptake their intake (Sheen, 2004). Previous studies revealed the possible link between corrective feedback and the uptake in different areas of language; for example, pronunciation (Sheen, 2004), lexical stress (Hassanzadeh & Salehizadeh, 2020), and identifying lexical categories in a virtual environment (Akiyama, 2019). Evaluating this particular link, revision through corrective feedback contributes to students' writing considerably.…”
Section: Theoretical Backgroundmentioning
confidence: 99%